HOBI REKREASIONAL DAN KETAHANAN KELUARGA MUSLIM: ANALISIS FUN FOOTBALL DALAM PERSPEKTIF HUKUM KELUARGA ISLAM STUDI KASUS JUVENTUS BOYOLALI - Kurniadi; Muhammad Ayub Afiffudin (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines the relationship between the hobby of recreational football and household harmony among Muslim families in the Juventus Boyolali community. The primary concern lies in the potential distortion of domestic relationships resulting from unmanaged recreational activities. Using a qualitative case study approach, data were collected through interviews, observations, and documentation, then analyzed using Miles and Huberman’s model and validated through triangulation. The findings indicate that recreational football does not inherently have a negative impact. On the contrary, the activity can support physical health, mental well-being, and family emotional stability when managed through proportional time allocation, open communication, and clear prioritization of obligations. The novelty of this research lies in exploring contemporary amateur sports as a tool for strengthening family resilience, rather than merely as a physical activity. The theoretical contribution enriches studies in Islamic Family Law and Muslim Family Sociology by integrating the values of mas’ūliyyah (responsibility) and mu‘āsyarah bi al-ma‘rūf (proper social conduct) in managing the husband’s private space (third space). The study concludes that household harmony is determined by relational maturity and internalization of Islamic values, rather than the mere presence of hobbies.